The Hearing Voices Movement in the United States: Findings from a national survey of group facilitators. Issue 2 (2nd April 2016) - Jones, Nev; Marino, Casadi "Khaki"; Hansen, Marie C.
Abstract : Empirical research on naturalistic hearing voices movement groups (HVG) has been limited to date. In an effort to better understand facilitator perspectives and variations in the structure of groups in the USA, we conducted a facilitator-led national survey of HVG facilitators. The survey included both close-ended and open-ended questions and was available online for 1 year. Participants were asked about the structure and composition of their groups, their perspectives on membership, clinician involvement, facilitator training and perceived impact of group participation on members. Thirty-two facilitators participated. The results underscore the diversity of HVG in the USA. The authors highlight three findings of interest: (1) participants' disagreements or uncertainty regarding a narrower HVG focus on experiences that would traditionally be described as "sensory hallucinations" versus a broader subset of extreme or unusual experiences (including "beliefs"); (2) tensions regarding HVG collaboration with clinicians; and (3) insights into impact.